Sage, Hero, Ironist: Sublimity and Irony in Thomas Carlyle’s Sartor Resartus and Lectures on Heroes - Novikova, Nataliya (Hungarian Journal of English and American Studies, 2021)
The paper focuses on the complex interplay between sublimity and irony, explored through a parallel reading of Sartor Resartus and On Heroes, Hero-Worship and the Heroic in History by the Victorian philosopher and historian Thomas Carlyle. The essay shows how a common philosophical framework, firmly based on a sublime principle, is affected by the style and structure of the analyzed works: it finds total affirmation in one case (On Heroes), while it undergoes ironic subversion in the other (Sartor Resartus). Carlyle’s transcendental ideal is dramatically at odds with what he identifies as the delusions of language and history, therefore, it requires an unusual agency and extraordinary cognitive powers defined as “heroic” to transform the common individual and ordinary collective being. The “hero” in Sartor Resartus, however, is radically different from those in the lectures On Heroes: the value of his sublime experience is repeatedly questioned through the intervention of an editorial persona and the fragmentation of the text.  (NN)